SELF-EFFICACY IN MOTHERS WITH EMESIS GRAVIDARUM - Badriah, Badriah; Wahyuni, Santi (Journal of Maternity Care and Reproductive Health, 2024)
The prevalence of emesis gravidarum cases in the world is estimated to reach 85% while in Indonesia it reaches 50-90% (Prawirohardjo, 2010). The high incidence of emesis gravidarum cases results in discomfort and decreased quality of life. This study aims to determine the self-efficacy of pregnant women in overcoming symptoms of nausea and vomiting before and after being given prenatal education interventions. Research design: quasi experiment with one group pre-posttest design. The sample size in this study amounted to 30 respondents (pregnant women) in the first trimester with emesis gravidarum in the Pulmbon  Health Center working area in 2021. The research instrument was a questionnaire to measure the level of self-efficacy. Data analysis using the T test. Research results: the majority of self-efficacy levels before prenatal education were in the low category (86.7%), and after the intervention, the high level dominated (56.7%). Based on the results of statistical tests, it is known that prenatal education intervention has a significant effect on increasing the self-efficacy of pregnant women in overcoming the symptoms of emesis gravidarum (α=0.001 <0.005). Conclusion: Self-efficacy of mothers with emesis gravidarum has increased after being given prenatal education. More sample size needed in future research.